2022
DOI: 10.1590/0001-3765202220200825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of partial 12S rRNA, 16S rRNA, COI and Cytb gene sequence datasets for potential single DNA barcode for hylids (Anura: Hylidae)

Abstract: We evaluated the extent of intraspecific and interspecific genetic distances and the effectiveness of predefined threshold values using the main genes for estimates of biodiversity and specimens' identification in anurans. Partial sequences of the mitochondrial genes for small (12S) and large (16S) ribosomal subunits, cytochrome c oxidase subunit I (COI) and Cytochrome b (Cytb) of the family Hylidae were downloaded from GenBank and curated for length, coverage, and potential contaminations. We performed analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…26 Our findings indicated that CRKA317 was not closely related to K. aerogenes ( Figure 2A ). The use of 16S rRNA gene for species identification presents significant challenges in interpretation because of its hypervariable domains ( Koroiva and Santana, 2022 ). Nevertheless, this approach allowed for an assessment of its relationship in the broader context of the genus.…”
Section: Resultsmentioning
confidence: 99%
“…26 Our findings indicated that CRKA317 was not closely related to K. aerogenes ( Figure 2A ). The use of 16S rRNA gene for species identification presents significant challenges in interpretation because of its hypervariable domains ( Koroiva and Santana, 2022 ). Nevertheless, this approach allowed for an assessment of its relationship in the broader context of the genus.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, DNA barcoding has become a widely used molecular technique for identifying species. This approach relies on sequencing a standardized fragment of DNA that can be compared to reference databases to accurately identify species (Gehara et al 2013;Koroiva & Santana 2022). DNA barcoding has also proven to be effective in delimiting species, and it has been applied across a wide range of taxa, including amphibians (Jansen et al 2011;Koroiva et al 2020;Koroiva & Santana 2022).…”
Section: J Ttmentioning
confidence: 99%